Antimicrobial Activity of Lemongrass Essential Oil (Cymbopogon flexuosus) and Its Active Component Citral Against Dual-Species Biofilms of Staphylococcus aureus and Candida Species - Gao, Shanjun; Liu, Guangzhi; Li, Jianguo; Chen, Jing; Li, Lina; Li, Zhen; Zhang, Xiulei; Zhang, Shoumin; Thorne, Rick Francis; Zhang, Shuzhen (Frontiers in Cellular and Infection Microbiology, 2020)
Compared to mono-species biofilm, biofilms formed by cross-kingdom pathogens are more refractory to conventional antibiotics, thus complicating clinical treatment and causing significant morbidity. Lemongrass essential oil and its bioactive component citral were previously demonstrated to possess strong antimicrobial efficacy against pathogenic bacteria and fungi. However, their effects on polymicrobial biofilms remain to be determined. In this study, the efficacy of lemongrass (Cymbopogon flexuosus) essential oil and its bioactive part citral against dual-species biofilms formed by Staphylococcus aureus and Candida species was evaluated in vitro. Biofilm staining and viability test showed both lemongrass essential oil and citral were able to reduce biofilm biomass and cell viability of each species in the biofilm. Microscopic examinations showed these agents interfered with adhesive characteristics of each species and disrupted biofilm matrix through counteracting nucleic acids, proteins and carbohydrates in the biofilm. Moreover, transcriptional analyses indicated citral downregulated hyphal adhesins and virulent factors of Candida albicans, while also reducing expression of genes involved in quorum sensing, peptidoglycan and fatty acids biosynthesis of S. aureus. Taken together, our results demonstrate the potential of lemongrass essential oil and citral as promising agents against polymicrobial biofilms as well as the underlying mechanisms of their activity in this setting.